ANALISIS PENGARUH TATA KELOLA PERUSAHAAN TERHADAP TINGKAT UNDERPRICING PENAWARAN UMUM PERDANA SAHAM (Studi Empiris terhadap Perusahaan Non Finansial di Bursa Efek Indonesia) - Bangkit Sasongko; Agung Juliarto (Diponegoro Journal of Accounting, 2014)
Underpricing phenomenon often occurs when a company undergoes an Initial Public Offering (IPO) in the stock market. Underpricing occurs when the initial public offering price is lower than the first day stock's closing price on the secondary market. Characteristics of corporate governance within the company may affect the investment behavior of investors, thus also affect the IPO pricing strategy. This study aims to analyze the influence of the corporate governance characteristics on the level of IPO underpricing. This research refers to research conducted by Darmadi and Gunawan (2013) and Filatotchev and Bishop (2002). The prior study used board size, board independence, ownership concentration and institutional ownership to analyze the corporate governance affect on underpricing. In this study, managerial ownership is added as independent variable on research model. The purpose is to investigate if and how the influence of share ownership by manager to management decision in determining the IPO price. Overall, this study uses five independent variables: i.e. the number of commissioner, commissioner independence, ownership concentration, managerial ownership, institutional ownership, and three control variables: ROE, firm size and underwriter reputation.Research population comprise all non-financial companies that was underpriced on IPO for the period 2006-2013. A Total population of 58 companies was used in analysis. Hypotheses in this study indicate that board size, commisioner independence, ownership concentration, managerial ownership, and institutional ownership partially affect the level of underpricing. This study uses Ordinary Least Square (OLS) Regression for hypotheses testing.Results of this study showed that the number of commissioner and institutional ownership negatively affected the level of underpricing. Ownership concentration had a positive effect on the level of underpricing. This study, did not find significant effects of commissioner independence and managerial ownership on the level of IPO undepricing. The implications of this study showed that the implementation of corporate governance can reduce the determination of the discount rate that used by company as signal of firm quality to investor on IPO.